In the shoes of accounting students: Perceptions of the skills needed for a successful career - Lopes, A. I.; Vinagre, F. (Journal of International Business Education, 2022)
Students are an important stakeholder group in higher education institutions (HEIs). This paper aims to examine students’ perceptions of the most important skills for a successful career in the accounting profession, and to identify how these perceptions vary among students with different academic profiles. Focusing on undergraduate and masters students, the analysis of the data indicate that perceptions differ according to students’ educational accounting profiles (level of education, professional experience, and business school excellence). The results show that students are clearly aware of the skill sets required by recruiters, but assign them varying levels of importance. The results have practical implications for academia (enhancing the perceived skills to meet objectives), recruiters (contributing to shaping the skills of aspirants), and students (matching their views with that of industry requirements).